2017
DOI: 10.1007/s12350-016-0534-z
|View full text |Cite
|
Sign up to set email alerts
|

Advances in image reconstruction software in nuclear cardiology: Is all that glitters gold?

Abstract: The cornerstone results of nuclear cardiology in the last 25 years were obtained with the Filtered Back Projection as the preferred reconstruction method for tomographic studies. Recently, evolution of the OSEM iterative reconstruction algorithms was implemented by different vendors. The value and limitations of the new methods are briefly addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…Using an anthropomorphic phantom already considered in previous publications, 9 – 11 a stress PD was simulated in different myocardial territories and acquired with a Cadmium-Zinc-Telluride (CZT)-based camera and a conventional gamma camera, with the filter-back projection (FBP) algorithm or an iterative algorithm with resolution recovery.…”
Section: Methodsmentioning
confidence: 99%
“…Using an anthropomorphic phantom already considered in previous publications, 9 – 11 a stress PD was simulated in different myocardial territories and acquired with a Cadmium-Zinc-Telluride (CZT)-based camera and a conventional gamma camera, with the filter-back projection (FBP) algorithm or an iterative algorithm with resolution recovery.…”
Section: Methodsmentioning
confidence: 99%
“…Procedures that utilize radionuclides, should be performed in accordance with the ALARA principle: 'As Low As Reasonably Achievable' in order to keep the radiation dose as low as possible. During the last years, clinical research have demonstrated that radiation dose in SPECT imaging can be reduced due new technical advances in hardware and improved reconstruction algorithms [2][3][4][5][6][7][8]. Most modern software uses maximum-likelihood (ML) based iterative reconstruction algorithms [9].…”
Section: Introductionmentioning
confidence: 99%
“…These algorithms were improved by incorporating attenuation correction, physical modeling of collimator and detector, as well as resolution recovery. It was demonstrated clinically that the improved algorithms provide good image quality despite reduced counting statistics [2][3][4][5][6][7][8]. Unfortunately the ML approach has fundamental limitations in solving reconstruction problems with limited data since unexpected artifacts may arise despite advanced processing techniques.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation